Delivery of Standardized Patient Instructions in the After-Visit Summary Reduces Telephone Calls Between Clinic Visits. (November 2018) - Deeds, Stefanie; Carr, Stephanie; Garrison, Michelle; Fainstad, Tyra
Telephone calls from patients can be a large source of between-visit work in outpatient clinics. A baseline audit at the study clinic identified medication refills and test results as the most common preventable calls. The authors created a dot phrase with standardized text detailing methods for refilling medications and reviewing test results and instructed providers to use it in the after-visit summary (AVS). After implementation of the AVS dot phrase, telephone calls for medications and results had an adjusted absolute decrease of 23.9 (95% CI = 15.4-32.4) calls per day to 16.2 (SD 7.7) calls per day, a relative reduction of 61%. Providers reported significantly fewer inbox requests for both refills ( P = .04) and test results ( P = .01). Using a standardized AVS dot phrase to inform patients on how to navigate care needs can significantly reduce between-visit workload for clinic staff and providers.